1986
DOI: 10.1590/s0071-12761986000100009
|View full text |Cite
|
Sign up to set email alerts
|

Estudos preliminares da biologia floral de Chrysophyllum Auratum Miq.(sapotaceae) em Piracicaba, estado de São Paulo

Abstract: Com a finalidade de contribuir para o conhecimento da biologia floral de Chrysophyllum auratum Miq. (SAPOTACEAE), foram estudados dois indivíduos cultivados no Setor de Horticultura da Escola Superior de Agricultura "Luiz de Queiroz", Piracicaba - SP. Observou-se a fenologia floral e propôs-se identificar o sistema de reprodução. As flores apresentaram ânteses vespertina e noturna, havendo protandria. Um dos indivíduos estudados mostrou-se precoce em relação ao outro, na maioria dos eventos fenológicos. A sínd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
1
4
0
4
Order By: Relevance
“…Data from the mineral analysis of wild Q. dumosa shoot tips and first leaves ( Table 1 ) showed detectable amounts of N, B, Ca, Cu, S, Fe, Mg, Mn, K, P, and Zn as a % of the total mass of the sample. We used three methods [ 12 , 13 , 14 , 16 ] to formulate three basal salt formulas based on the three methods ( Table 2 ). Notably, the mineral analysis only detected total N, but not whether it was in the form of NH 4 + or NO 3 − .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the mineral analysis of wild Q. dumosa shoot tips and first leaves ( Table 1 ) showed detectable amounts of N, B, Ca, Cu, S, Fe, Mg, Mn, K, P, and Zn as a % of the total mass of the sample. We used three methods [ 12 , 13 , 14 , 16 ] to formulate three basal salt formulas based on the three methods ( Table 2 ). Notably, the mineral analysis only detected total N, but not whether it was in the form of NH 4 + or NO 3 − .…”
Section: Resultsmentioning
confidence: 99%
“…Although many species grow well in these basal salts, there is great interspecific and intra-specific variation in performance on the media [ 9 , 10 , 11 ]. Several studies found successful methods of calculating new basal salt formulations based on the mineral analysis of field tissue, though each method is distinctly different [ 12 , 13 , 14 , 15 , 16 ]. Monteiro et al [ 12 ] found that passionfruit ( Passiflora edulis ) grown in vitro showed frequent leaf bleaching and reduced growth.…”
Section: Introductionmentioning
confidence: 99%
“…Tal fato é corroborado pelas observações de visitantes nas fl ores semi-abertas (forma tubular), com estilete exteriorizado e pela presença de grãos de pólen germinando na fase feminina em fl ores polinizadas naturalmente. Em Sapotaceae também há registros de dicogamia protândrica para as espécies Chrysophyllum auratum Miquel e C. oliviforme L. (Tomlinson 1974, Corrales et al 1986. Heslop-Harrison & Shivanna (1977) propuseram uma classifi cação para os estigmas de Angiospermas baseados nas características anatômicas e fi siológicas de suas superfícies, cobrindo cerca de 1000 espécies, de 900 gêneros, em 250 famílias.…”
Section: Discussionunclassified
“…Penn., e protandria para Chrysophyllum auratum Miq. (Corrales et al 1986) e C. oliviforme L. (Tomlinson 1974).…”
Section: Introductionunclassified
“…Há registro de que Manilkara subsericea e Sideroxylon obtusifolium são visitadas por insetos das ordens Hymenoptera, Lepidoptera, Coleoptera, Diptera e Thysanoptera (Gomes et al 2010), Chrysophyllum auratum é visitada por trips e moscas (Corrales et al 1986) e Pouteria venosa (Martius) Baehni é polinizada por dípteros e coleópteros noturnos (Gomes & Pinheiro 2007).…”
Section: Introductionunclassified